2020
DOI: 10.29146/eco-pos.v23i2.27397
|View full text |Cite
|
Sign up to set email alerts
|

Representações sociais sobre as mulheres rurais nas fotografias da revista Globo Rural (1985-2015)

Abstract: O objetivo deste estudo é analisar as representações sociais sobre as mulheres rurais veiculadas pela revista Globo Rural. O corpus é composto por 208 fotografias referentes a 30 edições da revista, temporalmente distribuídas entre os anos de 1985 e 2015. A metodologia orienta-se pela perspectiva documental, tendo como técnica a análise de conteúdo fotográfica. Com base na Teoria das Representações Sociais, identificam-se como resultados representações ancoradas na família, na culinária, na cultura e no trabal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Continuing education actions, such as the offer of postgraduate courses, have been subsidized by the Ministries of Health and Education, since the mid-1990s 23 . Unlike permanent education actions, those do not offer conditions for the true re ection on professional roles in the face of the reality of health services 24 . In the present study, no signi cant difference was observed in relation to the CI and ECTE results, when comparing the results of professionals with or without specialization in public health or family health.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing education actions, such as the offer of postgraduate courses, have been subsidized by the Ministries of Health and Education, since the mid-1990s 23 . Unlike permanent education actions, those do not offer conditions for the true re ection on professional roles in the face of the reality of health services 24 . In the present study, no signi cant difference was observed in relation to the CI and ECTE results, when comparing the results of professionals with or without specialization in public health or family health.…”
Section: Discussionmentioning
confidence: 99%